2018
DOI: 10.3390/biom8030069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calcium in Inflammation-Associated Bone Resorption

Abstract: The aim of this mini-review is to discuss the role of calcium in the process of cytokine-mediated bone resorption in an effort to understand the role circulating calcium may play in the resorption of bone. The liberation of calcium and possibly phosphorus and magnesium by bone resorption may sustain and intensify the inflammatory response. We used a burn injury setting in humans and a burn injury model in animals in order to examine the effects on the bone of the systemic inflammatory response and identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…CaSR upregulation reduces the set point for circulating calcium suppression of PTH secretion. Thus, a lower circulating calcium concentration, even concentrations in the hypocalcemic range, would be sufficient to reduce PTH secretion and, as a consequence, to decrease serum calcium (Klein, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CaSR upregulation reduces the set point for circulating calcium suppression of PTH secretion. Thus, a lower circulating calcium concentration, even concentrations in the hypocalcemic range, would be sufficient to reduce PTH secretion and, as a consequence, to decrease serum calcium (Klein, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although not always consistent (Toribio et al, 2005;Merriman et al, 2018), hypoparathyroidism (Nielsen et al, 1997;Holowaychuk et al, 2012), increased circulating calcitonin and procalcitonin (Müller et al, 2000;Bonelli et al, 2018), and decreased 1,25-(OH) 2 D concentrations (Waldron et al, 2003;Holowaychuk et al, 2012) are observed in immunoactivated states. Cytokines released during infection upregulate the parathyroid Ca sensing receptor, reducing the threshold necessary for suppression of parathyroid hormone secretion (Hendy and Canaff, 2016;Klein, 2018), resulting in hypocalcemia concurrently with hypoparathyroidism. Even if hormonal regulation favors hypocalcemia during immune activation, the acute decrease in Ca is likely too rapid to be explained by these mechanisms (Waldron et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also demonstrated that Vit D has the anti‐inflammatory properties (Mausa et al., 2016). In addition, the role of calcium modulating inflammation‐mediated resorption was also been recently discussed by Klein (2018). Therefore, next to evaluate the anti‐inflammatory potential of UVB‐ME treatment against the LPS‐induced inflammatory response (Jung et al., 2020), we decided to pre‐treat the zebrafish embryo with 5 and 10 µg/ml of UVB‐ME for 24 hr and then exposed to LPS (100 µg/ml) until 5 dpf to evaluate its anti‐inflammatory property.…”
Section: Resultsmentioning
confidence: 93%